2014
DOI: 10.1111/jopy.12104
|View full text |Cite
|
Sign up to set email alerts
|

Personality Predicts Obedience in a Milgram Paradigm

Abstract: This study investigates how obedience in a Milgram-like experiment is predicted by interindividual differences. Participants were 35 males and 31 females aged 26-54 from the general population who were contacted by phone 8 months after their participation in a study transposing Milgram's obedience paradigm to the context of a fake television game show. Interviews were presented as opinion polls with no stated ties to the earlier experiment. Personality was assessed by the Big Five Mini-Markers questionnaire (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 57 publications
3
44
1
1
Order By: Relevance
“…Note that, however, in this study, this was also the case for conscientiousness, which suggests that the associations of both big five factors with opposition to euthanasia may reflect social conformity- see Bègue et al, 2015- rather than necessarily empathy, compassion, and valuing no harm. Another argument in favor of a positive link between prosocial dispositions and the disapproval of child euthanasia may be that strong concerns for children’s capacity for discernment, typical among the skeptics (Bovens, 2015; Siegel et al, 2014), and subsequent fears of possible abuses of legalization (Karlsson, Strang, & Milberg, 2007), reflect high perspective taking, an important component of empathy.…”
Section: Other-oriented Emotions and Motivescontrasting
confidence: 50%
“…Note that, however, in this study, this was also the case for conscientiousness, which suggests that the associations of both big five factors with opposition to euthanasia may reflect social conformity- see Bègue et al, 2015- rather than necessarily empathy, compassion, and valuing no harm. Another argument in favor of a positive link between prosocial dispositions and the disapproval of child euthanasia may be that strong concerns for children’s capacity for discernment, typical among the skeptics (Bovens, 2015; Siegel et al, 2014), and subsequent fears of possible abuses of legalization (Karlsson, Strang, & Milberg, 2007), reflect high perspective taking, an important component of empathy.…”
Section: Other-oriented Emotions and Motivescontrasting
confidence: 50%
“…To begin with, previous research on the relationship between the self-concept and its outcomes has provided evidence for sociocul tural assimilation and contrast (Gebauer et al, in press;Gebauer, Leary, et al, 2012;Gebauer, Paulhus, et al, 2013). Moreover, as described earlier, there is much indirect evidence for links between these two sociocultural motives and the Big Five (Begue et al, 2014;Buss, 1991;Costa & McCrae, 1992;Cote & Moskowitz, 1998;DeYoung, 2006;DeYoung et al, 2002;John & Srivastava, 1999;K. B. MacDonald, 1995;Paulhus & John, 1998;Roberts & Pomerantz, 2004;Saucier, 2009;Wood et al, 2007).…”
Section: Previous Evidencementioning
confidence: 84%
“…Aside from a small‐sample post‐experimental inquiry by Elms and Milgram (), this research was never conducted, and five decades later, exactly why some individuals obey and others break off has long been a major unanswered question. However, Begue et al (in press) have recently observed low but significant correlations between measures of two personality traits (conscientiousness and agreeableness) and harmful obedience in a game‐show replication of Milgram's paradigm. They conclude, interestingly, that traits which are “widely related to positive outcomes…may also have darker sides in that they can lead to destructive and immoral obedience” (p. 15).…”
Section: Unanswered Questions In the Obedience Literaturementioning
confidence: 98%